2014
DOI: 10.3168/jds.2014-7927
|View full text |Cite
|
Sign up to set email alerts
|

Blood calcium dynamics after prophylactic treatment of subclinical hypocalcemia with oral or intravenous calcium

Abstract: Total serum Ca dynamics and urine pH levels were evaluated after prophylactic treatment of subclinical hypocalcemia after parturition in 33 multiparous Jersey × Holstein crossbreed cows. Cows were blocked according to their calcemic status at the time of treatment [normocalcemic (8.0-9.9 mg/dL; n = 15) or hypocalcemic (5.0-7.9 mg/dL; n = 18)] and randomly assigned to 1 of 3 treatments: control [no Ca supplementation (n = 11)]; intravenous Ca [Ca-IV (n = 11), 500 mL of 23% calcium gluconate (10.7 g of Ca and 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 19 publications
(28 reference statements)
5
54
0
5
Order By: Relevance
“…10 Another study comparing intravenous (IV) and oral calcium supplementation found that, while IV calcium led to earlier and higher peak serum calcium levels, oral calcium supplementation was associated with higher serum calcium between 20 and 48 hrs post-treatment. 11 Further, treatment with a calcium-containing bolus post calving was associated with a lower incidence of subclinical hypocalcemia, improved pregnancies per breeding, shorter days to pregnancy, and higher milk production in multiparous cows. [12][13][14] Other researchers have found equivocal effects of oral calcium supplementation on serum calcium, health, and reproductive outcomes.…”
Section: Introductionmentioning
confidence: 91%
“…10 Another study comparing intravenous (IV) and oral calcium supplementation found that, while IV calcium led to earlier and higher peak serum calcium levels, oral calcium supplementation was associated with higher serum calcium between 20 and 48 hrs post-treatment. 11 Further, treatment with a calcium-containing bolus post calving was associated with a lower incidence of subclinical hypocalcemia, improved pregnancies per breeding, shorter days to pregnancy, and higher milk production in multiparous cows. [12][13][14] Other researchers have found equivocal effects of oral calcium supplementation on serum calcium, health, and reproductive outcomes.…”
Section: Introductionmentioning
confidence: 91%
“…Blood Ca concentration increases rapidly with intravenous administration, peaking within 15 minutes of administration (Braun and others 2009). Subcutaneous administration is also acceptable for those unable to access a vein; however, time to peak Ca is extended to four hours (Blanc and others 2014, Domino and others 2017). The above treatment will provide the required Ca, and the cow will often stand within 30 minutes of administration.…”
Section: Hypocalcaemia (Milk Fever)mentioning
confidence: 99%
“…Short-term postpartum management strategies to prevent or treat hypocalcemia are often integrated in farm protocols and include Ca boluses (Sampson et al, 2009), drenches (Goff and Horst, 1993), or voluntarily consumed oral Ca supplements (Geishauser et al, 2008), as well as subcutaneous (Goff, 1999) or i.v. infusions (Blanc et al, 2014). These practices represent a therapeutic intervention more than a prevention strategy, and the implications of these strategies for metabolism and health require consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Treating cows with i.v. Ca infusions is the most direct intervention method to correct hypocalcemia and is understood to be an easy and inexpensive solution, although it may delay the adaptation of Ca metabolism, even inducing hypocalcemia in initially healthy animals (Martín-Tereso and Martens, 2014;Blanc et al, 2014). Intravenous Ca (11 g of Ca) is therefore not recommended for treating cows that are still standing (Oetzel, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation